Randomized study of washing 40‐ to 42‐day‐stored red blood cells. Issue 10 (16th April 2014) - Bennett‐Guerrero, Elliott; Kirby, Brett S.; Zhu, Hongmei; Herman, Annadele E.; Bandarenko, Nicholas; McMahon, Timothy J.
<x xml:space="preserve">Abstract</x> Background Pretransfusion washing of red blood cells (RBCs) stored for a longer duration may have theoretical advantages but few data exist to support this practice. In many hospital settings, use of a point‐of‐care cell washer could conceivably be used to quickly wash allogeneic RBCs before transfusion. The purpose of this preliminary study was to compare a point‐of‐care device with a common blood bank device for washing longer‐stored RBCs. Study Design and Methods Forty RBC units stored for 40 to 42 days were randomized to washing with the COBE 2991 device (Terumo BCT; FDA‐cleared for washing stored RBCs) or the Cell Saver Elite (Haemonetics; FDA‐cleared point‐of‐care device for processing and washing fresh autologous shed whole blood). Supernatant and unit RBCs from unwashed (baseline) and washed blood were assayed for potassium, lactate, intracellular ATP, percentage of RBC recovery, cell‐free hemoglobin, RBC microparticles, and RBCs were examined for susceptibility to hemolysis by physical stress. Results Both devices recovered a high percentage of RBCs and efficiently removed extracelluar potassium. Washing with the Elite resulted in significant increases in cell‐free Hb, percent hemolysis, and RBC microparticle production, whereas washing with the COBE 2991 did not (fold Δ = 2.1 vs. 1.0, 4.6 vs. 1.2, 2.0 vs. 1.1, respectively; p < 0.05). Hemolysis induced by physical stress was not altered by washing. Conclusion Although point‐of‐care washing of longer‐stored RBCs is appealing, these preliminary data suggest that transfusion of washed, longer‐stored units could result in potentially greater exposure to plasma free Hb. More data are needed before this practice can be routinely recommended.